2000
DOI: 10.1021/jo000266o
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of PAPS for the Enzymatic Synthesis of Sulfated Oligosaccharides

Abstract: This paper describes the study of 3'-phosphoadenosine-5'-phosphosulfate (PAPS) regeneration from 3'-phosphoadenosine-5'-phosphate (PAP) for use in practical syntheses of carbohydrate sulfates which are catalyzed by sulfotransferases. Among the regeneration systems, the one with recombinant aryl sulfotransferase proved to be the most practical. This regeneration system was coupled with a sulfotransferase-catalyzed reaction, using a recombinant Nod factor sulfotransferase, for the synthesis of various oligosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 48 publications
2
86
0
3
Order By: Relevance
“…Chitobiose was arbitrarily chosen as the integer value because of its low specificity constant with respect to the other three chitooligomers. The relative reaction specificity of the four substrates determined by our assay was in excellent agreement with that reported in the literature [31,37], which suggests that in the pathway of Nod signal biosynthesis, the lipochitotetrasaccharide Nod factor is preferably sulfated by NodH.…”
Section: Individual Kinetic Measurementssupporting
confidence: 89%
See 1 more Smart Citation
“…Chitobiose was arbitrarily chosen as the integer value because of its low specificity constant with respect to the other three chitooligomers. The relative reaction specificity of the four substrates determined by our assay was in excellent agreement with that reported in the literature [31,37], which suggests that in the pathway of Nod signal biosynthesis, the lipochitotetrasaccharide Nod factor is preferably sulfated by NodH.…”
Section: Individual Kinetic Measurementssupporting
confidence: 89%
“…Employing a thin layer chromatography assay, Long et al [30] and Kondorosi and coworkers [31] discovered that NodST can sulfate biosynthetic chitooligosaccharides in addition to natural Nod factors, although with a lower reaction activity. Kinetic analyses with both Nod factors and chitooligosaccharides of different chain lengths revealed the highest binding affinity and best reaction activity of NodH for the appropriate tetrameric substrates, which guarantees the modification of the tetrameric Nod factor-the most active one in Rhizobium meliloti, and thus contributes to host specificity [31,37]. Kinetic constants for various chitooligosaccharides have been determined individually by Kondorosi and coworkers [31] and Wong et al [37], which indicated that chitotetraose is a better substrate than chitotriose, chitopentaose, or chitohexaose, while NodST's activity for chitobiose is more than one order of magnitude lower than that for the other four.…”
mentioning
confidence: 95%
“…First, highly active HS O-sulfotransferases were expressed in E. coli, in order to provide sufficient quantities of sulfotransferases. Second, the sulfotransfer reactions were coupled with the PAPS regeneration system that was developed by the Wong group (56). This strategy eliminates the inhibition effect of PAP.…”
Section: Chemoenzymatic Synthesis Of Hs With Biological Activitiesmentioning
confidence: 99%
“…The PAPS regeneration system utilizes arylsulfotransferase IV, which can converts PAP to PAPS as illustrated in Figure 6B. In addition, the PAPS regeneration system utilizes the p-nitrophenol sulfate PNPS as the sulfo donor and requires only catalytic amounts of PAP, thereby reducing the cost of synthesis by more than 1000-fold (56). Immobilized enzymes are used in this approach for reuse and improved thermal stability of the HS sulfotransferases.…”
Section: Chemoenzymatic Synthesis Of Hs With Biological Activitiesmentioning
confidence: 99%
“…Next, modification reactions are undertaken relying on chemical deprotection and modification, and enzymatic modification using sulfotransferases and epimerase. Since half of the mass of heparin is sodium sulfate and the remainder is carbohydrate, a large amount of sulfo donor 3 0 -phosphoadenosine-5 0 -phosphosulfate (PAPS) is required, and as reactions are scaled up, this typically requires cofactor recycling (Burkart et al 2000; Fig. 1).…”
Section: Synthetic Methods Strategymentioning
confidence: 99%